Exploring the use of blockchain and smart contracts in the language services industry - Jakúbková, Nadežda (2022)
Commercial use of blockchain technology is no longer a domain of FinTech as its being examined and adopted across different fields. With its variety of technologies, the language services industry tends to be at the forefront of the early examination of new, revolutionary technologies. However, blockchain is yet to be added to this extensive repertoire. The thesis examines the use of blockchain and smart contracts in the language services industry, specifically in translation workflows. The main focus of the thesis is on the aspect of transparency and how the use of blockchain and smart contracts in the translation process can improve it. The thesis first examines academic resources on blockchain technology and smart contracts and explores the development of the language services industry and the impact of technology development on the industry. A blockchain-powered translation workflow model is introduced, and an application using blockchain technology is developed and described as a proof-of-concept. The application is evaluated, and model limitations are presented toward the end of the thesis.